Training guide configuring advanced Windows server 2012 services - Thomas, Orin 1973- (Microsoft Press, 2013)
Configuring Advanced Windows Server 2012 Services Designed to help enterprise administrators develop real-world, job-role-specific skills--this Training Guide focuses on advanced configuration of services necessary to deploy, manage and maintain a Windows Server 2012 infrastructure. Build hands-on expertise through a series of lessons, exercises, and suggested practices--and help maximize your performance on the job. This Microsoft Training Guide: Provides in-depth, hands-on training you take at your own pace Focuses on job-role-specific expertise for deploying and managing advanced infrastructure services in Windows Server 2012 Creates a foundation of skills which, along with on-the-job experience, can be measured by Microsoft Certification exams such as 70-412 Sharpen your skills. Increase your expertise. Configure full forest and domain trust relationships Configure Active Directory (AD) sites and manage AD replication Implement advanced DNS and DHCP solutions Install, configure, and manage AD Certificate Services Manage backups and recover servers Optimize storage and configure advanced file services Manage failover clustering and Network Load Balancing Move virtual machines from one Hyper-V server to another Implement Dynamic Access Control and Active Directory RMS Implement Active Directory Federation Services.
Online resource; title from title page (Safari, viewed Jan. 21, 2014)
Keywords: Microsoft Windows server; Operating systems (Computers); Systèmes d'exploitation (Ordinateurs); operating systems